Relationship between digital culture and autonomous learning in general studies students of a private university from Lima - Cosi Cruz, Elizabeth (2020)
The health crisis generated by COVID-19 has changed all our ways of life, including those that are linked to education, going from a teaching presence to a virtual one and that has highlighted the need to advance signicantly in the incorporation of the new technologies in the educational process. In this scenario, the present research aimed to determine the correlations between digital culture and autonomous learning in students of the rst years of a private university in Lima during 2020. For this purpose, a research design was used non-experimental of correlational scope. The study sample was probabilistic and consisted of a total of 352 students, who were administered two assessment instruments: Marina Kriscautzky's digital culture inventory and Mercedes López-Aguado's autonomous learning questionnaire. The statistical results achieved show the existence of signicant and positive correlations between both variables (r = 0,83), as well as signicant correlations between the various dimensions of digital culture and the various dimensions of autonomous learning.